MPLA shows attenuated pro‐inflammatory properties and diminished capacity to activate mast cells in comparison with LPS. Issue 10 (8th July 2015) - Schülke, S.; Flaczyk, A.; Vogel, L.; Gaudenzio, N.; Angers, I.; Löschner, B.; Wolfheimer, S.; Spreitzer, I.; Qureshi, S.; Tsai, M.; Galli, S.; Vieths, S.; et al.
Abstract Background Monophosphoryl lipid A (MPLA), a nontoxic TLR4 ligand derived from lipopolysaccharide (LPS), is used clinically as an adjuvant in cancer, hepatitis, and malaria vaccines and in allergen‐specific immunotherapy. Nevertheless, its cell‐activating effects have not been analyzed in a comprehensive direct comparison including a wide range of different immune cells. Therefore, the objective of this study was the side‐by‐side comparison of the immune‐modulating properties of MPLA and LPS on different immune cells. Methods Immune‐activating properties of MPLA and LPS were compared in human monocytes and mast cells (MCs), a mouse endotoxin shock model (ESM), and mouse bone marrow (BM)‐derived myeloid dendritic cells (mDCs), T cells (TCs), B cells, and MCs. Results In a mouse in vivo ESM and a human ex vivo monocyte activation test (MAT), MPLA induced the same cytokine secretion pattern as LPS (ESM: IL‐6, IL‐12, TNF‐α; MAT: IL‐1β, IL‐6, TNF‐α), albeit at lower levels. Mouse mDCs and ex vivo isolated B cells stimulated with MPLA required a higher threshold to induce TRIF‐dependent cytokine secretion (IL‐1β, IL‐6, IL‐10, and TNF‐α) than did LPS‐stimulated cells. In mDC:DO11.10 CD4 TC cocultures, stimulation with MPLA, but not with LPS, resulted in enhanced OVA‐specific IL‐4 and IL‐5 secretion from DO11.10 CD4 TCs. Unexpectedly, in both human and mouse MCs, MPLA, unlike LPS, did not elicit secretion of pro‐inflammatory cytokines. Conclusions Compared to LPS, MPLA induced a qualitatively similar, but less potent pro‐inflammatory immune response, but was unable to activate human or mouse MCs.